Impact of Money Laundering on Economic System: International Legal Framework and Corresponding Development in Pakistan - Hassan, Ali (Law and Policy Review, 2024)
This doctrinal mode study, based on the “Black Letter Law Method” aimed to identify the socio-economic existence, impacts, and severity of offence of Money Laundering (ML) and global regulatory response to cope with various emerging forms of ML. The study further aimed to analyze the legislative upgradations and legal setup of the Anti-Money Laundering (AML) regime in Pakistan. The operational and governance model of its Financial Intelligence Unit was also examined as well as its capacity to cope with trade-based ML offences in purview of modern practices. The study concluded that ML is an offence as much as a social norm affecting the economy through its various predicate and derivative offences and socially deep-rooted forms. Major over-hauling in operational and enforcement regime of the current Anti-Money Laundering Law of Pakistan is necessarily required. This is because it is not effective in timely detecting and combating the growing trends of ML related offences in a country striving for better economic performance, specifically offences pertaining to trade-based money laundering (TBML). The administrative model of the Financial Intelligence Unit of Pakistan, also known as the Financial Monitoring Unit (FMU), is governed under the AML Act 2020. It holds various lacunas in terms of the lack of horizontal coordination mechanism among the reporting entities, as well as centralized administrative control of FMU by the political representatives which hinders its operational, administrative, and regulatory autonomy. Moreover, there is insufficient technical expertise within the regulatory mechanism as well as incomplete and ineffective regulatory coverage over a number of business and financial sectors within the jurisdiction, coupled with the absence of standardized regulations, and non-enrollment of FMU by a global governing body.